The Effectiveness of Sleep Hygiene on Sleep Quality Cancer Patients Undergoing Chemotherapy: A literature Review - Setia, Vovi Meidas; Rosa, Elsye Maria (Universitas Aisyah Pringsewu, 2024)
Cancer occurs due to disruption of the function of Deoxyribonucleic Acid (DNA) which can increase cell growth significantly to cell proliferation in cells. The purpose of this study was to provide information on effective sleep hygiene therapy on the sleep quality of cancer patients undergoing chemotherapy. The research method using the PRISMA database using Google Scholar, PubMed, ScienceDirect, ProQuest and Scopus data focuses on the last five years, from 2018 to 2023. Data is selected by referring to the